Pemetaan Jalur Evakuasi dan Titik Kumpul dalam Upaya Mewujudkan Desa Pijot Yang Tanggap Bencana - Siti Maryam Ulfa Ulfa; Dipo Ario Kusuma; Arni Emiza Febrianti; Rosiatul Ismi; Siti Nuriah; Nurul Zainiyah; Rina Nuranjanisa; Soraya Rosanti; Ni Komang Eva Yuniasih; Tiara Hesti Amanda; Mila Andara; Lalu Sumardi (Universitas Mataram, 2022)
Disaster is an event or series of events which caused human suffering, loss of property, damage to the environment, facilities and infrastructure and can cause disruption to the life and livelihood of the community. Pijot Village is one of the areas located on the coast of the island of Lombok with a height of 500 meters above sea level and a rainfall rate of 491 mm, it makes this area often affected by disasters. This is certainly something that should be wary of, considering that disasters can happen at any time, so there is a need for disaster mitigation, namely visualization/mapping of disaster evacuation routes. The expected goal of this service activity is the existence of an evacuation route, which is devoted to tidal floods, earthquakes and tsunamis, and it is hoped that the evacuation route will be the best means that can facilitate the community in evacuating themselves when a disaster occurs.